(untitled) (Global Media Journal - German Edition, 2012)
Investigation of journalism’s role as writer and rewriter of the record of political episodes of world importance is central to this article, which takes an empirical approach in choosing the Danish press coverage of The Arab Spring as its starting point. The article analyses how a number of historical references to, in particular, European revolutionary history from Eastern Europe in 1989, are woven into the journalistic descriptions of events in Tunisia and Egypt. But the analysis also reflects on journalism’s own historical precedents in that field. Therefore, this paper takes the topics and circumstances that put Tunisia and Egypt on the Danish media’s agenda in the year before the Arab revolutions as a starting point. The central point of this comparison is to convey how journalism, while describing contemporary events of The Arab Spring, at the same time rewrites its own prior commentary on the region. Rewriting history in this way gives journalism a neutral and unassailable position as observer of events of world-wide importance, but it brings in its train other problems with staying true to both the readers and to unfolding events.